VARIASI BAHASA SEGI PENUTUR PADA KOMUNIKASI JUAL BELI DI PASAR SOCAH BANGKALAN - Ida Wati; Ika Febriani (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this research is to describe the variation of language in terms of speakers in buying and selling communication in the Socah Bangkalan market. This study uses a descriptive qualitative method with data collection through observation, free listening, speaking, recording, and taking notes. The analysis technique of this research is in the form of differentiating reactions and audibility levels. The results of the study contained data from December-February in the form of Madurese language variations, Javanese variations, and mixed language variations. Language variations in terms of speakers in buying and selling communication at the Socah Bangkalan market are found to have idiolects, dialects, and sociolects. Idiolects are variations of Madurese, Javanese, and mixed languages. There is a dialect of the Madurese language. This variation discusses the speaker's personal problems based on work. Based on occupation, including variations of buying and selling language used by traders and buyers in Socah Bangkalan market. So, based on sociolects, it includes colloquial levels of ngoko, Iya-Enja', and Enghi-Enten.